Dilated cardiomyopathy in children: determinants of outcome. Issue 3 (September 1994) - Burch, M; Siddiqi, S A; Celermajer, D S; Scott, C; Bull, C; Deanfield, J E
Abstract : OBJECTIVE–To determine the outcome of dilated cardiomyopathy presenting in childhood and the features that might be useful for prognostic stratification. SETTING–Supraregional paediatric cardiology unit. DESIGN–Retrospective analysis. BACKGROUND–The natural history of dilated cardiomyopathy in children is not well characterised. Previous studies have shown a variable relation between age at presentation and outcome, and sudden death has been infrequent. METHODS–Retrospective study of 63 consecutive patients with idiopathic dilated cardiomyopathy presenting between 1979 and 1992. Survival curves were constructed by the Kaplan-Meier method. RESULTS–Age at diagnosis ranged from 1 day to 15 years (median 12 months) and follow up ranged from 1 day to 13 years (median 19 months). Actuarial survival from presentation was 79% at one year (95% confidence interval (95% CI) 66%-88%) and 61% (44%-74%) at five years. Univariate analysis showed that mural thrombus, left ventricular end diastolic pressure > 20 mm Hg, and age at presentation > 2 years were predictors of adverse outcome, but on multivariate analysis only age at presentation was significant. Left ventricular echocardiographic indices either did not improve or deteriorated in 36 children (17 of whom died, four suddenly, and three were transplanted), partially improved in 16 (three of whom died, all suddenly), and returned to normal in 11 (all of whom have survived). CONCLUSIONS–Older age at presentation and lack of improvement in systolic function are associated with an adverse outcome, and early transplantation should be considered in these patients. There is a persistent risk of late sudden death in those children in whom echocardiographic dimensions remain abnormal.